FRI0339 Development of a Novel Patient Reported Outcome (PRO) Measure: The Systemic Lupus Erythematosus (SLE) Steroid Questionnaire (SSQ). (9th June 2015) - Mathias, S.D.; Berry, P.; deVries, J.; Askanase, A.; Pascoe, K.; Colwell, H.; Chang, D.
Abstract : Background: Many SLE patients receive oral glucocorticoids (steroids) as part of their treatment regimen. While providing symptom relief, most patients experience short- and long-term side effects associated with steroid use. Objectives: To develop a PRO to assess benefits, side effects, and impact associated with steroid use in SLE patients. Methods: Following IRB approval, 6 US rheumatology practices enrolled SLE patients with current or recent (past year) steroid use to participate in concept elicitation (CE) interviews about their steroid experience. A draft SSQ was developed, cognitively debriefed (CD) with SLE subjects, and finalized based on patient feedback, clinical input and a translatability assessment (an evaluation to assure words can be easily translated into other languages). Results: 33 subjects (95% female, 55% Caucasian, 25% African American, mean age 47 years, 52% moderate/severe SLE) completed CE interviews. Subjects reported symptom improvement and increased energy. Common side effects included weight gain (67%), swelling/moon face (36%), and mood swings/feelings of rage (21%). Most subjects (67%) would be happier if steroids were discontinued. During CD interviews (n=13), the SSQ was found to be comprehensive, clear, and relevant. Minor revisions were made to improve clarity. Key results from CE interviews and a summary of the final SSQ content are provided below. Conclusions: The SSQ is the first comprehensive PRO, developed with significant patient and clinical input, to assess SLE patient experience of oral steroid use. Its measurement properties will be evaluated in the future. Acknowledgements: The research presented in this abstract was funded by GlaxoSmithKline, USA. Disclosure of Interest: S. D. Mathias Consultant for: GlaxoSmithKline, P. Berry Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, J. deVries Shareholder of: GlaxoSmithKline, A. Askanase Consultant for: GlaxoSmithKline, K. Pascoe Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, H. Colwell Consultant for: GlaxoSmithKline, D. Chang Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline